2018
DOI: 10.3390/en11102842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerodynamic Interactions of Closely-Placed Vertical Axis Wind Turbine Pairs

Abstract: In this study, a numerical model was developed to study the effects of aerodynamic interactions between a pair of counter-rotating vertical axis wind turbines (VAWTs) in close proximity. In this model, the rotor rotation is not prescribed as a constant as in most other studies, but is determined by the moment of inertia and the total torque of the rotor, including the aerodynamic torque, generator torque, and a torque representing friction. This model enables study of the behavior of the rotor under an arbitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Some examples which use CFD to investigate the nature of VAWT wake characteristics are Samsoddin and Porte-Angel [15], who used a large eddy simulation approach for the investigation of wake characteristics behind a VAWT in a three-dimensional turbulent flow, and Bremseth and Duraisamy [7], who utilized the OVERTURNS solver and performed calculations using the solution of compressible URANS to simulate a single, paired, and array of VAWTs to conclude that a pair of counter-or co-rotating VAWTs were able to produce more power compared to an isolated turbine, taking advantage of the induced velocity field of the paired turbines. Peng [16], meanwhile, used OPENFOAM, open source CFD software utilizing the finite volume method, to compare the performance of two closely placed VAWT pairs and an isolated turbine. He concluded that the pairs of opposite-rotating turbines exhibit faster rotation compared with the isolated rotor in the same wind speed, hence a 70% performance improvement was noticed at a 1.6 equivalent turbine diameter spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples which use CFD to investigate the nature of VAWT wake characteristics are Samsoddin and Porte-Angel [15], who used a large eddy simulation approach for the investigation of wake characteristics behind a VAWT in a three-dimensional turbulent flow, and Bremseth and Duraisamy [7], who utilized the OVERTURNS solver and performed calculations using the solution of compressible URANS to simulate a single, paired, and array of VAWTs to conclude that a pair of counter-or co-rotating VAWTs were able to produce more power compared to an isolated turbine, taking advantage of the induced velocity field of the paired turbines. Peng [16], meanwhile, used OPENFOAM, open source CFD software utilizing the finite volume method, to compare the performance of two closely placed VAWT pairs and an isolated turbine. He concluded that the pairs of opposite-rotating turbines exhibit faster rotation compared with the isolated rotor in the same wind speed, hence a 70% performance improvement was noticed at a 1.6 equivalent turbine diameter spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Vergaerde et al (2019) experimentally showed that when two-bladed H-type Darrieus VAWT are installed next to each other in a plane normal to a uniform inflow, the power is increased by 16% compared to the output by two separate VAWT [105]. The closer the VAWT rotors are located, the stronger the effect is, which can reach nearly 70% at the rotor diameter to the distance between the rotors ratio d/D = 1.6 [106].…”
mentioning
confidence: 99%